1998
DOI: 10.1046/j.1365-2141.1998.01093.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of antenatal and perinatal variables on cord blood haemopoietic stem/progenitor cell yield available for transplantation

Abstract: Summary.We investigated the impact of maternal and fetal variables on cord blood (CB) haemopoietic stem/progenitor cell content. These included maternal age, ethnic origin, parity, ABO and Rhesus D blood group, antenatal haemoglobin, alcohol and cigarette consumption at time of registration, mode of delivery, duration of the first and second stages of labour, gestational age, birth weight, cord pH and cord erythrocyte mean cell volume (MCV). Cord volumes and total nucleated cellularities (TNC) were recorded, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 9 publications
(13 reference statements)
6
66
1
Order By: Relevance
“…This association is strongest with CD34 þ CD38 À cells, a relatively primitive haematopoietic stem cell population. These data are in line with previous studies, which showed a positive relationship between cord blood CD34 þ or CFU-GM levels and birth weight (Shlebak et al, 1998;Ballen et al, 2001;Aroviita et al, 2004). However, in our study, newborns in the lowest birth weight category (o3000 g) can have higher levels of stem/progenitor cell measurements than those with 3000 -3499 g birth weight resulting in a J-or U-shaped relation between stem cell levels and birth weight.…”
Section: Discussionsupporting
confidence: 92%
“…This association is strongest with CD34 þ CD38 À cells, a relatively primitive haematopoietic stem cell population. These data are in line with previous studies, which showed a positive relationship between cord blood CD34 þ or CFU-GM levels and birth weight (Shlebak et al, 1998;Ballen et al, 2001;Aroviita et al, 2004). However, in our study, newborns in the lowest birth weight category (o3000 g) can have higher levels of stem/progenitor cell measurements than those with 3000 -3499 g birth weight resulting in a J-or U-shaped relation between stem cell levels and birth weight.…”
Section: Discussionsupporting
confidence: 92%
“…[12][13][14][15][16][17][18][19] UCB collection is performed during the final phase of labor or, more commonly, after delivery of Correspondence: Dr MJ Laughlin, Case Western Reserve University, University Hospitals Ireland Comprehensive Cancer Center, 11100 Euclid Avenue, Wearn 433, Cleveland, Ohio 44106-5065, USA Table 1 Advantages of UCB as hematopoietic stem cells for allogeneic transplantation 1 Placental or umbilical cord blood is an abundantly available source of stem cells which can be harvested at no risk to the mother or infant. 2 Ethnic balance in a cord blood repository can be maintained automatically in heterogeneous populations or can be controlled via collection from birthing centers representing targeted minority populations.…”
Section: Ucb Collection and Bankingmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19] UCB collection is performed during the final phase of labor or, more commonly, after delivery of…”
Section: Ucb Collection and Bankingmentioning
confidence: 99%
“…Indeed, the Bone Marrow Donors Worldwide collaboration of registries presents a lack of genetic diversity with an over-representation of donors from Northwestern European descent. 4,6,7,[10][11][12][13][14] Thus, patients with non-European ancestry have lower odds of obtaining a graft with high HLA compatibility and/or high TNCC. [13][14][15][16] These studies highlight the importance of developing CB banking in partnership with birth clinics that care for pregnant women originating from populations that are underrepresented in existing CBBs and registries.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that volume and TNC and progenitor counts are correlated. [6][7][8][9][10] Besides CBU cell content, a central issue of CB banking raised by many authors is HLA diversity. Indeed, the Bone Marrow Donors Worldwide collaboration of registries presents a lack of genetic diversity with an over-representation of donors from Northwestern European descent.…”
Section: Introductionmentioning
confidence: 99%